Biphen[n]arenes. Issue 1 (6th October 2014) - Chen, Huanqing; Fan, Jiazeng; Hu, Xiaoshi; Ma, Junwei; Wang, Shilu; Li, Jian; Yu, Yihua; Jia, Xueshun; Li, Chunju
Abstract : We describe the one-pot synthesis, unique geometries and intriguing host–guest properties of a new class of supramolecular macrocycles – biphen[ n ]arenes ( n = 3, 4). Abstract : To design and exploit novel macrocyclic synthetic receptors is a permanent and challenging topic in supramolecular chemistry. Here we describe the one-pot synthesis, unique geometries and intriguing host–guest properties of a new class of supramolecular macrocycles – biphen[ n ]arenes ( n = 3, 4), which are made up of 4, 4′-biphenol or 4, 4′-biphenol ether units linked by methylene bridges at the 3- and 3′- positions. The biphenarene macrocycles are conveniently accessible/modifiable and extremely guest-friendly. Particularly, biphen[4]arene is capable of forming inclusion complexes with not only organic cationic guests but also neutral π-electron deficient molecules. Compared with calixarenes, resorcinarenes, cyclotriveratrylenes and pillararenes with substituted mono-benzene units, the biphen[ n ]arenes reported here possess significantly different characteristics in both their topologic structures and their recognition properties, and thus can find broad applications in supramolecular chemistry and other areas.